(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Over the past two decades, the significance of responsible investing has surged, prompting a focus on understanding the interaction between Environmental, Social, and Governance (ESG) factors. This study investigates the relationship between stock returns, investment performance, and ESG considerations as investors increasingly prioritize sustainability in their decision-making processes. By analyzing a sample of NIFTY 50 companies listed on the National Stock Exchange (NSE), this research delves into how ESG factors influence stock returns and financial performance. Employing a comprehensive methodology, this study expands on previous research by incorporating financial performance metrics alongside stock returns. It seeks to shed light on the nuanced dynamics between ESG performance and financial outcomes within the context of NIFTY 50 companies. The FEM regression method was employed to examine how ESG rating affected corporate financial performance and stock returns. Notably, the findings underscore the substantial impact of environmental sustainability on stock returns and financial performance, reinforcing previous research in this area. Furthermore, the study highlights the significance of individual ESG components, including corporate governance standards and environmental regulations, in shaping investment outcomes. By elucidating the intricate relationship between ESG factors and financial performance, this research contributes valuable insights to the body of knowledge surrounding sustainable investing.